New usage of habenaria radiata as a cut flower - P. Sinumporn (2018)
Habeneria radiata is a small and elegant terrestrial orchid native to Japan. It has also been used as a potted plant. The aim of this work was to examine the possibility of H. radiata for use as a cut flower. In Japan, tubers of H. radiata sprout in early April and flower between late June and August. Plant height manipulation is required for adoption in a wide range of uses as a cut flower. Reducing light intensity is an easy and effective method to increase plant height; both 50 and 70% shading increased plant height of H. radiata by 30%. Uniconazole is an effective growth retardant, and application to the soil was more effective than a foliage spray. By controlling shading and the application of growth retardant, H. radiata can be produced at a plant height from 7 to 30 cm. Flower longevity is also an important factor for a successful cut flower. Silver thiosulfate (STS) pretreatment increased flower longevity of H. radiata, suggesting the flower is ethylene sensitive. Sucrose (1 to 3%) in a vase solution also enhanced flower longevity and produced larger sized flowers. STS-treated cut H. radiata flowers kept in a vase solution containing sucrose showed over two weeks vase life. Here, we discuss the potential of H. radiata as a new cut flower.